Quality Development in Health Care: Participation vs. Accreditation - Simonsen, Jesper; Hertzum, Morten; Scheuer, John Damm (Nordic Journal of Working Life Studies, 2018)
For more than a decade, quality development in the Danish health care sector has been managed with an accreditation system known as the Danish quality model (DQM), shaping the strategy for how to align work organization with technology use. In this article, we introduce a participatory design approach, known as effects-driven information technology development (EDIT), and discuss how this approach may contribute to a new quality-assurance program for the Danish health care sector. Our purpose is to demonstrate how accreditation, which focuses on processes and standards, needs to be supplemented and balanced with participatory approaches that allow for local experimentation and implementation of high-quality outcomes. We describe accreditation and participatory design as two approaches to reconfiguring and aligning work organization and technology; further, we emphasize the differences in each approach’s strategy and application.